2017
DOI: 10.20885/asjmc.vol1.iss1.art3
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Convergence: Challenges for Contemporary Media in Indonesia

Abstract: This paper examines the implications of media liberalization and media convergence to regulatory issues and journalism practices in Indonesia. While technologies are being used to serve the economic interests of media companies, corporate concentration and technological convergence effectively disempower media workers. It will do so through an in-depth analysis of the current trends and case studies in the Indonesian media industry. The Indonesian case shows how media liberalization affects Indonesian media la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
1
2
0
2
Order By: Relevance
“…In this case, we conclude that ownership become the factor that influence the Republika newsroom in delvier news about Inter Milan and Satria Muda Pertamina. This findings also confirmed with literatures that stated mass media is being used by the owner to accommodate their (the owner's) interest (Souisa, 2017). What Republika's done confirmed that when media companies also owning sport teams, it will affect the media content.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this case, we conclude that ownership become the factor that influence the Republika newsroom in delvier news about Inter Milan and Satria Muda Pertamina. This findings also confirmed with literatures that stated mass media is being used by the owner to accommodate their (the owner's) interest (Souisa, 2017). What Republika's done confirmed that when media companies also owning sport teams, it will affect the media content.…”
Section: Discussionsupporting
confidence: 84%
“…In Indonesia, a study about the influence of media ownership to the editorial policy, often talking about political themes (e.g. Souisa, 2017). This paper will discuss on a different issue, about the sport themes.…”
Section: Introductionmentioning
confidence: 99%
“…Sebagian perusahaan media baru lainnya, sedangkan sisanya adalah perusahaan media yang digolongkan sebagai usaha media rintisan (startup media). Teknologi konvergensi dan konglomerasi itu turut membentuk nilai profesional dan peran jurnalisme Indonesia kontemporer (Sumartias & Hafizni, 2017;Souisa, 2017;Dharmasaputra, 2011;Hanitzsch, 2005).…”
Section: Gilang Desti Parahitaunclassified
“…Industri TV menempati psosisi yang sangat penting bagi pemerintah Indonesia, karena berkontribusi terhadap ekonomi dan memberi manfaat bagi pembangunan nasional (Alfian, Chu, & Abdullah, 1981). Bagi pemerintah, penyiaran TV juga berguna untuk mempromosikan persatuan dan integrasi nasional (Kitley, 2000), serta menjaga pluralisme dan keragaman dalam masyarakat (Souisa, 2017). Indonesia adalah negara multikultural yang rawan konflik antar kelompok etnis (Zarbaliyev, 2017).…”
Section: Hasil Dan Pembahasan Nilai Penting Penyiaran Tv Bagi Indonesiaunclassified